Assessment of atypical pneumonia by chest ultrasonography - Ahmed Sameh Sayed; Mona Mansour Ahmed; Khaled Mohamed Wagih; Haytham Samy Diab; Ahmed Mohamed Hussein (The Egyptian Journal of Bronchology, 2023)
Abstract Background Patients with pneumonia exhibit similar clinical presentations despite having different causative organisms; thus, a rapid and easy test is needed to differentiate between the diseases. Here, we use lung ultrasound to discriminate between causative organisms in correlation with other diagnostic modalities. Methods This descriptive cross-sectional study was carried out on 67 patients diagnosed with atypical pneumonia admitted at Ain-Shams University hospitals in the period from July 2019 to June 2021. Study population was divided into three groups according to the causative agent based on the results of PCR: Group 1 included 23 patients (influenza A), group 2 included 30 patients (COVID-19), and group 3 included 14 patients (atypical organisms). Included patients underwent lung ultrasound scan via a 12-zone scanning protocol and CT scan with 24 h in between. The present study was approved by the ethical committee at our institution. Results The mean age ranged from 39.93 ± 19.26 SD to 60.3 ± 13.02 SD years; 64.17% of them were males. There was also a highly statistically significant difference between the three groups as regard B-lines and thickened pleural line being higher among group 2; 100% of cases had B-lines in their chest ultrasound assessment, while thickened pleural line was found in 53.3% of cases. Dynamic air bronchogram was found with higher percentage in group 3 (71.4%) with a highly significant association. Higher mean Soldati score was associated with more severe disease among cases with viral pneumonia. Conclusions Lung ultrasound may be used as an aiding tool to estimate the etiology of atypical pneumonia. It can be useful during pandemics of acute respiratory diseases for rapid triage and stratification of patients as through calculation of modified Soldati score and detection of the most common finding. Also, modified Soldati score correlates with disease severity.